Mediating the impact of innovation on the relationship between branding, organisational learning capability and SMEs performance. (6th January 2023) - Hafeez, Muhammad Haroon; Umrani, Waheed Ali; Shariff, Mohd Noor Mohd; Ahmed, Umair; Haroon, Uzma; Ramayah, T.
The purpose of this paper was to examine the relationship between branding and SME performance as well as organisational learning capabilities and SME performance. In addition, the current study also examines the indirect effect of innovation on the branding-SME performance relationship and the organisational learning capabilities-SME performance relationship. Using a survey method, data was collected from SME owners/managers of the Sports Industry in Sialkot, Pakistan. The questionnaire was adopted from the literature. The method of data collection was self-administration and a total of 346 responses were collected. Our results show support for a direct relationship between branding and SME performance as well as organisational learning capabilities and SME performance. Additionally, results revealed that innovation mediates the relationships between branding and SME performance as well as organisational learning capabilities and SME performance. This paper extends the body of knowledge by providing empirical evidence in favour of resource based view (RBV) theory, under which we found support for the hypothesised relationships.